Psychometric properties of the Assessment of Positive Occupation 15 final version in individuals with mental illness - Takuya Noguchi; Makoto Kyougoku (SAGE Publishing, 2021)
Aims This study was to test the reliability and validity of the Assessment of Positive Occupational 15 (APO-15) for individuals experiencing mental illness. Methods A sample of 408 people experiencing mental illness living in communities or admitted to hospitalized was recruited. The sample has completed demographic information, the Assessment of Positive Occupation 15 (APO-15), the Japanese version of the Self-identified Stage of Recovery Part-B (SISR-B), the Japanese version of the Recovery Assessment Scale (RAS), the General Health Questionnaire 12 (GHQ-12). APO-15 is a measure of how engaged one is in occupations that promote well-being. The final version of the APO-15 was developed by assessing the validity and reliability by mainly using confirmatory factor analysis (CFA), item response theory (IRT). Results This study indicated satisfactory the validity and reliability of APO-15 in a group of individuals experiencing mental illness. CFA showed acceptable values for all indices of fit, namely comparative fit index (CFI), Tucker-Lewis index (TLI) (i.e., greater than .90), and the value of root mean square error of approximation (RMSEA) was .087, which was acceptable. The IRT showed satisfactory responses for the item slope parameter (α) and item difficulty parameter (β) in APO-15. Discussion APO-15 was demonstrated good psychometric properties in measuring involvement in the occupation to promote well-being in individuals experiencing mental illness. In conclusion, the APO-15 is an important tool to enable occupational therapists to assess clients who are not engaged in well-being promoting occupations and thus enable them to participate in such occupations.